2005
DOI: 10.1523/jneurosci.0242-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus History Reliably Shapes Action Potential Waveforms of Cortical Neurons

Abstract: Action potentials have been shown to shunt synaptic charge to a degree that depends on their waveform. In this way, they participate in synaptic integration, and thus in the probability of generating succeeding action potentials, in a shape-dependent way. Here we test whether the different action potential waveforms produced during dynamical stimulation in a single cortical neuron carry information about the conductance stimulus history. When pyramidal neurons in rat visual cortex were driven by a conductance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 35 publications
5
77
0
Order By: Relevance
“…In addition to discharge rate, the shape of the action potential (Matsumura et al, 1995;de Polavieja et al, 2005;Gold et al, 2006) is also thought to reflect intrinsic changes in neuronal excitability (e.g., availability of sodium channels). We used the From top to bottom, The relationship between the mean corrected firing rate and the frequency of pauses; the relationship between the mean corrected firing rate and the mean pause duration; and the relationship between the mean corrected firing rate and the amount of time the cell was in a pause.…”
Section: Relationships Between Discharge Parameters and Pausesmentioning
confidence: 99%
“…In addition to discharge rate, the shape of the action potential (Matsumura et al, 1995;de Polavieja et al, 2005;Gold et al, 2006) is also thought to reflect intrinsic changes in neuronal excitability (e.g., availability of sodium channels). We used the From top to bottom, The relationship between the mean corrected firing rate and the frequency of pauses; the relationship between the mean corrected firing rate and the mean pause duration; and the relationship between the mean corrected firing rate and the amount of time the cell was in a pause.…”
Section: Relationships Between Discharge Parameters and Pausesmentioning
confidence: 99%
“…Action potential broadening is much more pronounced in mossy fiber boutons than in the calyx of Held in the auditory brainstem [11], implying that broadening is a specific property of cortical presynaptic terminals. This may suggest that information in the mossy fiber system is not only coded by action potential frequency and timing but also as action potential duration [25]. Second, recent experiments revealed that subthreshold excitatory postsynaptic potentials (EPSPs) can be passively propagated from the somatodendritic domain of granule cells to mossy fiber boutons [2].…”
Section: Abstract Presynaptic Recording Mossy Fiber Boutons Mossymentioning
confidence: 99%
“…Mostly in invertebrates, for example in leech segmental ganglia, crustacean stomatogastric ganglia or in insect visual pathways, but also in vertebrate nervous systems, neurons are known that convey information by signals that combine graded potential shifts with spikes of variable amplitude, termed in the following "mixed potential signals" (e.g. Hengstenberg, 1977;Graubard et al, 1980;Simmons, 1982;Arbas and Calabrese, 1987;Juusola et al, 1995;Awatramani et al, 2005;de Polavieja et al, 2005;Alle and Geiger, 2006;Shu et al, 2006;Juusola et al, 2007). It is tantalizing to suggest that coarse information (analogous to spike rate) may be carried by the graded component while temporally precise information is present in the timing of spikes of these mixed potential neurons.…”
mentioning
confidence: 99%
“…A combination of graded and spike-like signals in the axonal membrane potential has been shown to maximize information transmission (Haag and Borst, 1998;de Polavieja et al, 2005;Juusola et al, 2007).…”
mentioning
confidence: 99%